Voids’ layer structures in silicon irradiated with high doses of high-energy helium ions - Starchyk, M.I.; Marchenko, L.S.; Pinkovska, M.B.; Shmatko, G.G.; Varnina, V.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Structural and optical properties of single crystal silicon irradiated with 27.2 MeV helium ions by using fluences Ф ≥ 10¹⁶ ion/cm² were studied at various beam currents. It was found that at currents 0.25 to 0.45 μА, heavily damaged layers containing voids were formed in ion path in Si and behind it. The number of layers in the ion path region depends on the beam intensity. With increasing the beam current up to ~1 μA, the layer structures consisting of voids were observed only in the ion path. As helium is poorly soluble in Si, during implantation it collects in the gas-filled vacancy complexes. We consider that, like to the case of keV-ion implantation at fluences of Ф ≥ 10¹⁶ ion/cm² , an amorphous layer is created in the ion stopping region at annealing. Moving by recrystallization fronts on both sides of the amorphous layer, vacancy clusters are collected inside, coalesce and form voids. It is a combination of high energy and high fluence helium implantation that can form layered structure with voids in silicon, as observed by us. At present, there is no strict explanation of the mechanism of voids’ ordering (forming of superlattice of them). Especially, it concerns the void layer formation beyond helium ion path. The concept of mobile solitons is used. Formation of the “lattice” from the voids leads to swelling of the material. Further researches are necessary to understand these processes and control them.